A Practical and Enantiospecific Synthesis of (−)‐(R)‐ and (+)‐(S)‐Piperidin‐3‐ols. Issue 11 (18th November 2014) - Suresh Babu, Meruva; Raghunadh, Akula; Ramulu, Konda; Dahanukar, Vilas H.; Syam Kumar, Unniaran K.; Kumar Dubey, P.
Abstract A highly enantiospecific, azide‐free synthesis of (−)‐(R)‐ and (+)‐(S)‐piperidin‐3‐ol in excellent yield was developed. The key step of the synthesis involves the enantiospecific ring openings of enantiomerically pure (R)‐ and (S)‐2‐(oxiran‐2‐ylmethyl)‐1H‐isoindole‐1, 3(2H)‐diones with the diethyl malonate anion and subsequent decarboxylation.